Differential Sex-Dependent Regulation of the Alveolar Macrophage miRNome of SP-A2 and co-ex (SP-A1/SP-A2) and Sex Differences Attenuation after 18 h of Ozone Exposure - Nithyananda Thorenoor; David S. Phelps; Joanna Floros (MDPI AG, 2020)
Background: Human SP-A1 and SP-A2, encoded by SFTPA1 and SFTPA2, and their genetic variants differentially impact alveolar macrophage (AM) functions and regulation, including the miRNome. We investigated whether miRNome differences previously observed between AM from SP-A2 and SP-A1/SP-A2 mice are due to continued qualitative differences or a delayed response of mice carrying a single gene. Methods: Human transgenic (hTG) mice, carrying SP-A2 or both SP-A genes, and SP-A-KO mice were exposed to filtered air (FA) or ozone (O3). AM miRNA levels, target gene expression, and pathways determined 18 h after O3 exposure. RESULTS: We found (a) differences in miRNome due to sex, SP-A genotype, and exposure; (b) miRNome of both sexes was largely downregulated by O3, and co-ex had fewer changed (≥2-fold) miRNAs than either group; (c) the number and direction of the expression of genes with significant changes in males and females in co-ex are almost the opposite of those in SP-A2; (d) the same pathways were found in the studied groups; and (e) O3 exposure attenuated sex differences with a higher number of genotype-dependent and genotype-independent miRNAs common in both sexes after O3 exposure. Conclusion: Qualitative differences between SP-A2 and co-ex persist 18 h post-O3, and O3 attenuates sex differences.